From Guidance to Growth: Roles of Parental Involvement, Coping Strategies, and Psychological Meaningfulness in Career Decision-Making among High (Practicum Psychologia, 2026)
Although parental involvement, coping strategies, and psychological meaningfulness are widely acknowledged as key influences in youth development, limited empirical work has examined their roles within African educational contexts. We investigated the moderating roles of coping strategies, and PsyM in the relationship between parental involvement (PI) and career decision-making (CDM) among high school students. Four hundred and ninety-five (495) students (males: n = 255, 51.5%; females: n = 240, 48.5%; mean age = 16.5 years, SD = 1.7) were drawn from five Nigerian secondary schools using a cross-sectional design and convenience sampling approach. Participants completed the Parental Involvement Scale, the Brief COPE Inventory, the meaningfulness domain of The Meaning and Purpose Scales (MAPS), and the Career Decision-Making Scale. Results revealed that PI did not predict CDM among high school students. However, problem-focused coping was positively associated with CDM, whereas emotion-focused and avoidance coping were negatively associated with CDM in this population. PsyM did not predict career decision making. Furthermore, neither the coping strategies domains nor PsyM moderated the relationship between PI and career decision making in this group. Interventions aimed at enhancing CDM among high school students may benefit from strengthening problem-focused coping while addressing reliance on emotion-focused and avoidance strategies.